Expansão térmica sintonizável do ZrW2O8 - Jadna, Catafesta (My University, 2014)
Zirconium tungstate (a-ZrW2O8) exhibits isotropic negative thermal expansion over a wide range of temperature. Under high-pressures this material transforms to a metastable amorphous phase (a-ZrW2O8). a-ZrW2O8 can be fully recovered by annealing the amorphous phase at temperatures slightly above 600oC, at room pressure. The amorphous phase, in principle, should exhibit positive thermal expansion and, with the progressive recrystallization of the amorphous phase, it could be possible to obtain samples with tunable thermal expansion between the characteristic values of the amorphous and crystalline phases. It was exactly this possibility that was studied in this work. Samples of a-ZrW2O8 prepared at 7,7 GPa in a toroidal chamber in the Laboratório de Altas Pressões e Materiais Avançados at the Instituto de Física, Universidade Federal do Rio Grande do Sul, were submitted to successive heat treatments at different temperatures. X-ray diffraction measurements were performed in order to verify the occurrence of the phase transition (amorphous --> crystalline). The coefficient of thermal expansion of the samples of ZrW2O8 was determined using a thermomechanical analyzer. The results demonstrated the successful obtainment of crystalline-amorphous composites of ZrW2O8 with tunable thermal expansion coefficient between 7.5 x 10-6°C-1 and -9 x 10-6°C-1.
O tungstato de zircônio (a-ZrW2O8) exibe expansão térmica negativa e isotrópica em um amplo intervalo de temperatura. Em altas pressões este material se transforma em uma fase amorfa metaestável (a-ZrW2O8). A fase a-ZrW2O8 pode ser totalmente recuperada através de tratamentos térmicos com a fase amorfa a-ZrW2O8 em temperaturas acima de 600°C e pressão ambiente. A fase amorfa, em princípio, deve possuir expansão térmica positiva e, com a progressiva conversão para a fase a-ZrW2O8, deve ser possível a obtenção de amostras com expansão térmica sintonizável entre os valores característicos das fases amorfa e cristalina. Foi justamente este o problema científico abordado neste trabalho. Para tanto, amostras de a-ZrW2O8 foram preparadas a 7,7 GPa em uma câmara toroidal no Laboratório de Altas Pressões e Materiais Avançados do Instituto de Física da Universidade Federal do Rio Grande do Sul. Estas amostras foram submetidas a sucessivos tratamentos térmicos, em diferentes temperaturas. Medidas de difração de raios X foram realizadas para verificar a ocorrência da transição de fase (amorfa --> cristalina). O coeficiente de expansão térmica das amostras de ZrW2O8 foi determinado com o auxílio de um analisador termomecânico. Os resultados demonstraram a viabilidade da obtenção de compósitos cristalino-amorfo de ZrW2O8 com coeficiente de expansão térmica sintonizável entre 7,5 x 10-6°C-1 e -9 x 10-6°C-1.
Keywords: Cerâmica; Material cerâmico; Expansão térmica; Expansão térmica negativa; Tungstato de zircônio